STRATEGI PENGEMBANGAN ALAT TANGKAP DI KABUPATEN BANGKA TENGAH - Dareen Nadya Rema (JURNAL PERIKANAN DAN KELAUTAN, 2022)
Fishermen in Central Bangka Regency still use traditional fishing gear and simple technology. These types of fishing gear need to choose the best fishing gear as a form of optimizing the use of fish resources to find out the right fishing gear development strategy in Central Bangka Regency. Multi-criteria analysis (MCA) with four criteria of biological, technical, economic and social aspects, these results indicate that a sustainable fishing technology unit can be developed on priority one, namely fishing gear with a value of VA = 13.26, on the second priority, namely hand line with a value of VA = 12.87 and on the third priority, namely the bagan tancap with a value of VA = 11.56 and the first priority of the fishing gear development strategy is more directed to the strategy of developing facilities and infrastructure (WO) with a value of 0.309 followed by the second priority, namely the development of fishing gear (SO) with a value of 0.265 and the third priority is optimizing fishermen's cooperatives (ST) with a value of 0.247.